A Direct Method to Compare Bipolar LR Fuzzy Numbers. (14th March 2018) - Ghanbari, Reza; Ghorbani-Moghadam, Khatere; Mahdavi-Amiri, Nezam
Abstract : We propose a new method for ordering bipolar fuzzy numbers. In this method, for comparison of bipolar LR fuzzy numbers, we use an extension of Kerre's method being used in ordering of unipolar fuzzy numbers. We give a direct formula to compare two bipolar triangular fuzzy numbers in O ( 1 ) operations, making the process useful for many optimization algorithms. Also, we present an application of bipolar fuzzy number in a real life problem.